Comparison of 3D printed nose bolus to traditional wax bolus for cost‐effectiveness, volumetric accuracy and dosimetric effect - Christine Albantow; Catriona Hargrave; Amy Brown; Christopher Halsall (Journal of Medical Radiation Sciences, 2020)
Abstract Introduction Three‐dimensional printing technology has the potential to streamline custom bolus production in radiotherapy. This study evaluates the volumetric, dosimetric and cost differences between traditional wax and 3D printed versions of nose bolus. Method Nose plaster impressions from 24 volunteers were CT scanned and planned. Planned virtual bolus was manufactured in wax and created in 3D print (100% and 18% shell infill density) for comparison. To compare volume variations and dosimetry, each constructed bolus was CT scanned and a plan replicating the reference plan fields generated. Bolus manufacture time and material costs were analysed. Results Mean volume differences between the virtual bolus (VB) and wax, and the VB and 18% and 100% 3D shells were −3.05 ± 11.06 cm3, −1.03 ± 8.09 cm3 and 1.31 ± 2.63 cm3, respectively. While there was no significant difference for the point and mean doses between the 100% 3D shell filled with water and the VB plans (P> 0.05), the intraclass coefficients for these dose metrics for the 100% 3D shell filled with wax compared to VB doses (0.69–0.96) were higher than those for the 18% and 100% 3D shell filled with water and the wax (0.48–0.88). Average costs for staff time and materials were higher for the wax ($138.54 and $20.49, respectively) compared with the 3D shell prints ($10.58 and $13.87, respectively). Conclusion Three‐dimensional printed bolus replicated the VB geometry with less cost for manufacture than wax bolus. When shells are printed with 100% infill density, 3D bolus dosimetrically replicates the reference plan.